6y-54=60

Simple and best practice solution for 6y-54=60 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6y-54=60 equation:


Simplifying
6y + -54 = 60

Reorder the terms:
-54 + 6y = 60

Solving
-54 + 6y = 60

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '54' to each side of the equation.
-54 + 54 + 6y = 60 + 54

Combine like terms: -54 + 54 = 0
0 + 6y = 60 + 54
6y = 60 + 54

Combine like terms: 60 + 54 = 114
6y = 114

Divide each side by '6'.
y = 19

Simplifying
y = 19

See similar equations:

| 1/8(7+8z)=-1/4 | | 6x-5=6x-19 | | -80=1.8c+-11 | | v-8(2-2v)=-118 | | 1.5w-3=3+2w | | 5x-x=25 | | 2.9+0.7x=0.1 | | p+2p-7=-6p+8p | | -3(r+5)=-47 | | 16x+39=102 | | 5.8=4.5+z | | -7x-3=3x+67 | | 12x-5=-19 | | (-n)-24=5-n | | -4x=62 | | y+3/t=t*t | | 6x+10=7x | | 4(4x-1)-(5x+1)=2(x+5)-33 | | 1/2d-3d=2 | | -11=1.8c+-80 | | -0.20-0.44a=0.13 | | 19x-30=179 | | p-0.2t=s | | 2x^3-2x^2y-24xy^2= | | 3-c-12=-5+c | | 17=-7+3p | | 8x+1+27x+4=180 | | y=2/3(72)+4 | | 4(j-2)=32 | | 2.8x+5-3.8x=9 | | 3x+1=15x-107 | | -22.89=1.7m |

Equations solver categories